Sikap, Subyektif Normal, Dan Pengendalian Diri Untuk Terhadap Kinerja Agen Pemasaran Produk Hartal Mart - Ridwan; Achmad Firdaus; Mokhamad Yasid (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
The purpose of this study is to analyze the effect of attitude has a significant influence on agent intentions, the influence of subjective norms on agent intentions, the effect of self-control on agent intentions in marketing halal mart products. This study uses the Theory Planned Behavior method and structured equation modeling (SEM) to see the effect of agents on the intentions and performance of agents to market halalmart products through measurement in terms of attitudes, subjective norms and self-control. The results of the research data show that attitudes, subjective norms and self-control have a significant and positive influence on the intentions of the agents to improve performance in marketing halalmart products.